Evolution of the CO2 carrying capacity of CaO particles in a large calcium looping pilot plant. (July 2017) - Diego, M.E.; Arias, B.; Abanades, J.C.
Highlights: A method to estimate Xave based on mass and particle population balances is used. The calculated Xave are compared to the experimental values from a pilot plant. These values match when the calciner operates far from equilibrium conditions. Enhanced deactivation is observed when the calciner works close to equilibrium. Abstract: Post-combustion calcium looping is an emerging capture technology that uses CaO particles as CO2 sorbent. This work analyses the average maximum CO2 carrying capacity of the sorbent (Xave ) in a continuous large-scale calcium looping (CaL) pilot plant, which is believed to adequately represent the lifetime of CaO particles in larger CaL systems based on the regeneration of CaO by oxyfuel combustion in the calciner. The CO2 carrying capacity is a key variable in designing the CO2 capture carbonator reactor and for optimizing the performance of the system. Several experimental campaigns have been carried out in La Pereda 1.7 MWth pilot plant both under oxy-fired and air-fired combustion conditions, in which the evolution of Xave with time has been measured under a wide range of conditions in the calciner. A methodology based on a closure of mass and particle population balances has been used to estimate Xave . Closure of the sulphur balance was found to be very accurate as an internal calibration tool to quantify the make-up flow of limestone that effectively participates in the CO2 capture process in any given set of conditions. When the calciner reactor was operated in conditions far from the equilibrium of CO2 on CaO, a good agreement was found between the experimental Xave values and those calculated from population mass balances which account for the number of carbonation-calcination cycles of each particle. However, a CO2 carrying capacity lower than expected was observed in some tests in oxy-combustion mode when the calciner was operating close to equilibrium. Departure from ideal sorbent behavior and more intense deactivation was found to increase with longer residence times in the calciner (∼3 min). This deactivating effect may be due to the effective increase in the number of carbonation-calcination cycles of the particles, caused by switching between carbonating and calcining conditions inside the calciner when the reactor operates close to equilibrium. The results obtained in this study indicate that optimum operation of the calciner for sorbent activity is achieved in conditions sufficiently far from equilibrium and with low bed inventories (short particle residence time in the calciner).